Pendidikan Multikultural dalam Membentuk Karakter Toleransi di MI Ma'arif Caruy Cilacap - Uswatun (J-PGMI: Jurnal Pendidikan Guru MI, 2023)
The Indonesian nation is known for being a very multicultural nation, thus it is necessary to provide multicultural education in order to form the character of tolerance for every individual in Indonesia. With this very multicultural nation, multicultural education is very necessary for children from an early age with the aim of forming a character of tolerance in children. so that it can minimize students' intolerant attitudes from an early age. This research uses a qualitative descriptive research method. Data collection uses observation, interview and documentation techniques. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of this research are that multicultural education for MI Ma'arif Caruy students is provided through PPKN learning and the example of educators, so that through PPKN learning students can know the various kinds of diversity that each person has and through the teacher's example students can model how to tolerance in life.